2013
DOI: 10.1590/s0100-204x2013001200010
|View full text |Cite
|
Sign up to set email alerts
|

Predicting rapeseed oil content with near-infrared spectroscopy

Abstract: -The objective of this work was to establish a calibration equation and to estimate the efficiency of near-infrared reflectance (NIR) spectroscopy for evaluating rapeseed oil content in Southern Brazil. Spectral data from 124 half-sib families were correlated with oil contents determined by the chemical method. The accuracy of the equation was verified by coefficient of determination (R 2 ) of 0.92, error of calibration (SEC) of 0.78, and error of performance (SEP) of 1.22. The oil content of ten genotypes, wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 12 publications
0
4
0
1
Order By: Relevance
“…For each model, the validation set shows statistics very close to the calibration set, illustrating robustness and absence of overfitting of the models. Concerning oil content, the model described in this paper for Arabidopsis display better performance than the ones described for rapeseed (Tkachuk, 1981; Hom et al, 2007; Rossato et al, 2013). Interestingly, the models were developed on entire seeds without destruction neither any special sample preparation, which is a great advantage compared to calibration developed on powder or oil for example (Khamchum et al, 2013) as it’s faster and allow the seeds to be used for other applications.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…For each model, the validation set shows statistics very close to the calibration set, illustrating robustness and absence of overfitting of the models. Concerning oil content, the model described in this paper for Arabidopsis display better performance than the ones described for rapeseed (Tkachuk, 1981; Hom et al, 2007; Rossato et al, 2013). Interestingly, the models were developed on entire seeds without destruction neither any special sample preparation, which is a great advantage compared to calibration developed on powder or oil for example (Khamchum et al, 2013) as it’s faster and allow the seeds to be used for other applications.…”
Section: Discussionmentioning
confidence: 71%
“…In recent decades, NIRS has been widely used as a fast and reliable method for qualitative and quantitative analysis in many fields (Font et al, 2006) and International Standards Committees have formally accepted methods using NIRS for analysis of many compounds (Batten, 1998). Regarding Brassica seeds, many authors have reported NIRS models for different components, such as glucosinolates (Velasco and Becker, 1998; Font et al, 2004), fiber (Font et al, 2003), protein and oil contents (Tkachuk, 1981; Font et al, 2002a,b; Rossato et al, 2013). …”
Section: Introductionmentioning
confidence: 99%
“…[20][21][22] Modern instruments have incorporated Fourier-Transformation (FT) to NIR instruments (or FTNIR) to reduce the signal to noise ratio. 14,19,23 The use of FTNIR spectroscopy has been reported for the prediction of oil content, fatty acids, moisture, and protein in different plant species such as Brassica napus, [24][25][26] Camelina sativa, 27 Carthamus tinctorius, 23 Olea europaea, 10 Glycine max (soyabeans), 28 Paeonia sect Moutan, 13 Sesamum indicum, 29 Silybum marianum, 7 and Theobroma cacao 30 and Zea mays. 4 However, no studies have been conducted or reported on the utilization of FTNIR spectroscopy to analyse beauty leaf tree samples.…”
Section: Introductionmentioning
confidence: 99%
“…Seed research has been successful in evaluating quality, such as soybeans, cotton and tomato (Bazoni et al, 2017;Gaitán-Jurado et al, 2008;Huang et al, 2013;Shrestha et al, 2016), viability in maize and spinach (Ambrose et al, 2016;Shetty et al, 2012), composition and prediction of phytic acid in Vigna radiata (Pande and Mishra, 2015), nitrogen content in Vigna unguiculata (Ishikawa et al, 2017), oil composition in sunflower and canola (Grunvald et al, 2014;Rossato et al, 2013), as well as the classification of genotypes in cotton, barley, castor beans and maize (Cui et al, 2012;Jia et al, 2015;Ringsted et al, 2016;Santos et al, 2014;Soares et al, 2016).…”
Section: Introductionmentioning
confidence: 99%